Watercress oil loaded with gel: evaluation of hemolysis inhibition, antioxidant, antimicrobial, and healing properties - Alharbi, Bandar; Qanash, Husam; Almashjary, Majed N.; Barnawi, Heba; Aldarhami, Abdu; Alsaif, Ghaida; Alsamaan, Fahad; Monjed, Mohammad Khalil; Al Shmrany, Humood; Bazaid, Abdulrahman S. (Frontiers in Pharmacology, 2024)
Plant-derived compounds are renowned for their remarkable pharmacological properties, holding immense promise for therapeutic interventions in human health. In this study, we aimed to assess the antimicrobial, anti-hemolytic, antioxidant, and wound healing attributes of watercress oil incorporated into Vaseline gel (OLG) compared to watercress oil alone. OLG was formulated through a meticulous process involving the addition of Vaseline gel to the oil under agitation conditions. High-performance liquid chromatography analysis of watercress oil unveiled a rich array of phenolic compounds, including gallic acid (10.1821 µg/mL), daidzein (3.46 µg/mL), and hesperetin (3.28 µg/mL). The inhibitory zones caused by watercress oil alone against a spectrum of pathogens, including Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, Enterococcus faecalis, and Candida albicans, were measured at 25±0.